Ciência e jornalismo: a construção do sentido do discurso jornalístico-científico no texto verbal e não-verbal de reportagens da Revista Época - Calado, Liliane de Andrade (2012)
The science and its developments are part of human history. Nowadays, we see its evidence in our daily lives, from trivial actions, but also on complex issues such as human cloning. The media, in turn, recognizing the power of science has spread scientific advances in its support and is in accordance with this perspective that consolidates the production of scientific journalism, a practice that aims the dissemination of science under the auspices of journalistic standards . Thus, this study sought to understand the construction of texts of speeches verbal and nonverbal included in the section Science & Technology of the ÉPOCA magazine, which aims to disseminate scientific matters. To this end, we selected seven subjects in this section broadcast from January to December 2010. In analyzes, we apply the principles of greimasiana semiotics, which is based on the route generative methodological sense, which shows the production of meanings in the text heights. We seek to highlight the effects of meaning caused by discursive strategies chosen by the reporters as well as the joints that confirm the formation of these texts.